AB083. Does concomitant testosterone replacement improve the response of tadalafil 5 mg once daily in men with lower urinary tract symptoms? - Park, Nam Cheol (Transl Androl Urol, 2016)
OBJECTIVES: Recently, tadalafil was found to be effective for treating lower urinary tract symptoms (LUTS) secondary to benign prostatic hyperplasia (BPH). Testosterone (T) regulates nitric oxide synthase and is necessary to achieve an optimum response to PDE5 inhibitors. In the present study, we determined whether T replacement in men with low T levels receiving tadalafil to treat LUTS improved the response of tadalafil on LUTS. METHODS: The present 12-week study was a randomized parallel study of clinical outcomes in men aged ≥40 years with symptomatic BPH (IPSS ≥12), prostate volumes ≥30 mL, and testosterone levels less than 300 ng/dl. Eligible patients received a combination of tadalafil 5 mg once daily and placement of a transdermal gel containing 10 g T (n=44), or tadalafil alone (n=46). The primary outcomes were post-treatment IPSS, peak urinary flow rate, and post-void residual urine volume (PVR). Secondary outcomes were changes in IIEF-EF domain scores, Global Assessment Questionnaire (GAQ) scores, and Life Satisfaction Checklist (LSC) scores. RESULTS: The extent of IPSS improvement from baseline to 12 weeks was the same in both groups (tadalafil+T –5.2 vs. tadalafil –5.0; P=0.634). Also, the changes in Q(max) and PVR from baseline were very similar in both groups. However, the tadalafil+T group showed a significantly greater change from baseline in the IPSS storage subscore, the IPSS-QoL score, and the IIEF-EF domain score. The tadalafil+T group showed significantly greater improvements in GAQ and LSC scores, as compared to the tadalafil-only group. The adverse event profiles of each group were similar to those of previous reports. CONCLUSIONS: Tadalafil plus testosterone was superior to tadalafil alone in improving LUTS in men with BPH/LUTS and low testosterone levels. Further study is needed with more number of patients and longer duration study for support of present study.